Nos bastidores da ciência 20 anos depois - Sebastião J. Formosinho (Ciências e Culturas, 2007)
Though we might not think so from the media, the strongest area of science in Portugal is actually chemistry - the science of real life, which is also a "green science", closely connected to the radical transformation of life style that has considerably increased the life expectancy of mankind. Chemistry is not only the domain with the greatest productivity and scientific impact in Portugal, it is also the subject in which we have six universities in the top 1% in the world as regards scientific citations. Irrespective of the personal merit of Sebastião Formosinho and his team, it is not surprising that these scientists, by developing a new theoretical model (ISM) to estimate the velocity of molecular transformations - a model which went against the established knowledge on the subject - have for twenty years been offering a serious challenge to one of the paradigms that won the Nobel Prize in Chemistry in 1992 in the person of Prof. Rudolph Marcus. They also managed to "overcome" Nature when one of their boldest predictions, made in 1991, was confirmed and published in 2006. This effectively ended one round of this scientific battle, although the scientific community was not yet convinced of the validity of these ideas. Recently, however, there have been signs of change as some authorities in the chemistry world were gradually won round. This work offers a glimpse behind the scenes at knowledge in the making, a journey that involves autobiographical details, epistemological and sociological analysis, and scientific controversies, and which outlines the difficulties of producing science and making it past the Portuguese red tape. This is a story of strong contrasts and surprising perspectives, essential for anyone that wishes to understand what it means to be a scientist. The last chapter describes a hospitalization, told from the author's unique perspective, but with a certain amount of distance and with great humanization - for after all longevity is what comes to mind when we think of any route through the limelight.